Pengetahuan, Sikap, Dukungan dan Persepsi Konsumsi Tablet Tambah Darah (TTD) pada Mahasiswi Fakultas Kedokteran dan Ilmu Kesehatan Universitas Kristen Satya Wacana - Davidson, Sarah Melati; br Tampubolon, Vio Herawati; Tampubolon, Rifatolistia (HB PRESS, 2023)
Iron-deficiency anemia is a significant nutritional concern in Indonesia. This type of anemia is more common among children, adolescents, pregnant and breastfeeding women, and low-income workers. Although students from the Faculty of Medicine and Health Sciences have been informed about anemia and iron (Fe) tablets, there are still many who have not started taking them. This research aims to describe the knowledge, attitudes, support, and perception of Fe tablet consumption among female students at this University. The research used a descriptive-analytic method with a cross-sectional approach. The study population consisted of 93 female students from the 2021 batch, specifically from the Faculty of Medicine and Health Sciences. The research sample was selected based on inclusion and exclusion criteria. A questionnaire was used as the research instrument and analyzed using univariate analysis. The findings revealed that only 22.6% of the respondents reported consuming Fe tablets, while 77.4% did not. Twenty-six respondents displayed a good level of knowledge, and 31 had a positive attitude. The level of support from family and peers was low, with only 22 respondents reporting family support and 30 reporting peer support. Despite not taking iron tablets regularly, the respondents' knowledge, attitudes, perception of benefits, and constraints were generally in a good category. However, the support variable obtained still needs improvement as it remains in the low category, which contributes to the irregular intake of iron tablets by the respondents.